Measurement of charm meson lifetimes - Bonvicini, G; Cinabro, D; Greene, R; Perera, L; Zhou, G; Chan, S; Eigen, G; Lipeles, E; Schmidtler, M; Shapiro, A; Sun, WM; Urheim, J; et al. (1999)
We report measurements of the D0, D+, and Ds+ meson lifetimes using 3.7 fb-1 of e+e- annihilation data collected near the γ(4S) resonance with the CLEO detector. The measured lifetimes of the D0, D+ , and Ds+ mesons are 408.5 ± 4.1-3.4+3.5 fs, 1033.6 ± 22.1-12.7+9.9 fs, and 486.3 ± 15.0-5.1+4.9 fs. The precisions of these lifetimes are comparable to those of the best previous measurements, and the systematic errors are very different. In a single experiment we find that the ratio of the Ds+ and D0 lifetimes is 1.19 ± 0.04. © 1999 The American Physical Society.